2013
DOI: 10.1002/cphc.201201015
|View full text |Cite
|
Sign up to set email alerts
|

3D Nanoscale Chemical Imaging of the Distribution of Aluminum Coordination Environments in Zeolites with Soft X‐Ray Microscopy

Abstract: Which side are you on? Scanning transmission X-ray microscopy is used for the first time to elucidate the coordination and distribution of aluminum in industrial-relevant zeolites at the single-particle level. Extended regions of a few hundred nanometers, rich in higher aluminum coordination environments, are heterogeneously embedded within the zeolite particle, before and after a steaming post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…These differences have been observed before in similar fluorescence staining experiments of FCC particles, but the unique correlative approach presented here allows us now to unambiguously link reactivity to ultrastructure 5, 19. The differences seen in reactivity may be explained by differences in the distribution of Al coordination in the zeolite particles, which has been shown to vary within ZSM‐5 particles32 as well as in zeolite Y embedded in FCC catalysts 10. Furthermore, previous research has shown polarization dependence of the fluorescent products can also play a role in ZSM‐5 containing FCC particles, although this does not apply to reactivity differences within one zeolite domain 33.…”
supporting
confidence: 71%
“…These differences have been observed before in similar fluorescence staining experiments of FCC particles, but the unique correlative approach presented here allows us now to unambiguously link reactivity to ultrastructure 5, 19. The differences seen in reactivity may be explained by differences in the distribution of Al coordination in the zeolite particles, which has been shown to vary within ZSM‐5 particles32 as well as in zeolite Y embedded in FCC catalysts 10. Furthermore, previous research has shown polarization dependence of the fluorescent products can also play a role in ZSM‐5 containing FCC particles, although this does not apply to reactivity differences within one zeolite domain 33.…”
supporting
confidence: 71%
“…Our group has recently been applying STXM in the field of zeolite chemistry and catalysis. [25][26][27]77 Using this experience it was possible to observe the crystallization of the extra-framework AlPO 4 phase of H-mordenite in space and time by application of an in situ nanoreactor. 28 X-ray tomography was used to create a 3-D nanoscale chemical reconstruction of the AlPO 4 phase in a single H-mordenite aggregate for the first time.…”
mentioning
confidence: 98%
“…27,[87][88][89][90][91] In their detailed examination of aluminosilicate minerals, Li and coworkers developed assignments by comparing Al K-edge and Si K-edge spectra and using MO calculations of the AlO6 9-cluster.…”
Section: Figure 4 Al K-edge Xas Of Al Metal (Black Circles) Comparedmentioning
confidence: 99%